Bionic Silk Fibroin Film Promotes Tenogenic Differentiation of Tendon Stem/Progenitor Cells by Activating Focal Adhesion Kinase - Kang Lu; Xiaodie Chen; Hong Tang; Mei Zhou; Gang He; Zhisong Lu; Kanglai Tang (Stem Cells International)
Background. Tendon injuries are common musculoskeletal disorders in clinic. Due to the limited regeneration ability of tendons, tissue engineering technology is often used as an effective approach to treat tendon injuries. Silk fibroin (SF) films have excellent biological activities and physical properties, which is suitable for tendon regeneration. The present study is aimed at preparing a SF film with a bionic microstructure and investigating its biological effects. Methods. A SF film with a smooth surface or bionic microstructure was prepared. After seeding tendon stem/progenitor cells (TSPCs) on the surface, the cell morphology, the expression level of tenogenic genes and proteins, and the focal adhesion kinase (FAK) activation were measured to evaluate the biological effect of SF films. Results. The TSPCs on SF films with a bionic microstructure exhibited a slender cell morphology, promoted the expression of tenogenic genes and proteins, such as SCX, TNC, TNMD, and COLIA1, and activated FAK. FAK inhibitors blocked the enhanced expression of tenogenic genes and proteins. Conclusion. SF films with a bionic microstructure may serve as a scaffold, provide biophysical cues to alter the cellular adherence arrangement and cell morphology, and enhance the tenogenic gene and protein expression in TSPCs. FAK activation plays a key role during this biological response process.